2018
DOI: 10.1186/s13568-018-0590-7
|View full text |Cite
|
Sign up to set email alerts
|

Eukaryal composition and diversity in anaerobic soils influenced by the novel chiral insecticide Paichongding

Abstract: Paichongding (IPP) is a neonicotinoid chiral insecticide with independent intellectual property in China. IPP application can increase crop yield, and also lead to insecticide residue and pollution in soils, which will affect microbial population and community composition in soils. In this study, four different types of soils were employed to inquire into the impact of IPP on eukaryal community and species-group through pyrosequencing of 18S rRNA gene amplicons. Fungal population differed in different soils at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In anaerobic soil, paichongding had been found to inhibit bacterial diversity as well as growth (Cai et al, 2015) and the soil bacterial community composition varied at both phylum and genus levels (Cai et al, 2015;Cai et al, 2016a). Paichongding also caused significant differences in eukaryal population before and after application and it could cause some phyla and genera to grow or shrink in anaerobic soils (Zhu et al, 2018). Five studies (17%) reported that acetamiprid, imidacloprid, paichongding and thiamethoxam inhibited soil enzymatic activities (cellulase, urease, dehydrogenase, catalase, phosphatase and phosphomonoesterase) ultimately hampering biogeochemical function of soil such as ammonification, nitrification and denitrification (Cai et al, 2016a;Castillo Diaz et al, 2017;Filimon et al, 2015;Wang et al, 2014).…”
Section: Neonicotinoid Studies That Reported No Adverse Effect On The...mentioning
confidence: 99%
“…In anaerobic soil, paichongding had been found to inhibit bacterial diversity as well as growth (Cai et al, 2015) and the soil bacterial community composition varied at both phylum and genus levels (Cai et al, 2015;Cai et al, 2016a). Paichongding also caused significant differences in eukaryal population before and after application and it could cause some phyla and genera to grow or shrink in anaerobic soils (Zhu et al, 2018). Five studies (17%) reported that acetamiprid, imidacloprid, paichongding and thiamethoxam inhibited soil enzymatic activities (cellulase, urease, dehydrogenase, catalase, phosphatase and phosphomonoesterase) ultimately hampering biogeochemical function of soil such as ammonification, nitrification and denitrification (Cai et al, 2016a;Castillo Diaz et al, 2017;Filimon et al, 2015;Wang et al, 2014).…”
Section: Neonicotinoid Studies That Reported No Adverse Effect On The...mentioning
confidence: 99%